Land reclamation recovery with the sewage sludge use - Tamanini,Cristina Rincon (2008)
In this work, investigations were carried out with five treatments [control, three doses of lime stabilized sludge (60, 120, 240 Mg ha-1 dry base) and soil corrective plus mineral fertilizer] to evaluate the immediate recuperation of a borrowed area. The application of stabilized alkaline sewage sludge acted as an acidity corrective, allowed the increase in the organic matter contents (21 to 43.5g dm-3) and available P (44 to 156 mg dm-3). Even with the use of the highest dose, no increase in the concentration of 32 analyzed metals was observed, due to the low concentration of metals in the sludge. The experiment showed that short term restoration of degraded area was possible by using high rates of sewage sludge without metal contamination.